2009
DOI: 10.2215/cjn.00930209
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Renal Transplantation

Abstract: Background and objectives: Renal transplant recipients experience premature cardiovascular disease and death. The association of inflammation, all-cause mortality, and cardiovascular events in renal transplant recipients has not been examined in a large prospective controlled trial.Design, setting, participants, & measurements: ALERT was a randomized, double-blind, placebo-controlled study of the effect of fluvastatin on cardiovascular and renal outcomes in 2102 renal transplant recipients. Patients initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 50 publications
5
83
2
Order By: Relevance
“…More novel markers such as asymmetric dimethylarginine, which is associated with endothelial dysfunction, are also associated with higher risk of mortality (HR = 2.18) and developing CVD (HR = 2.59) in ESRD [140] . Poorer graft outcomes are predicted by IL-6 [136,141] and elevated symmetric dimethylarginine [142] (HR = 5.51). TroponinT, usually used in the diagnosis of ACS, is a strong independent predictor of allcause mortality in stable RTRs [143] .…”
Section: Inflammationmentioning
confidence: 99%
“…More novel markers such as asymmetric dimethylarginine, which is associated with endothelial dysfunction, are also associated with higher risk of mortality (HR = 2.18) and developing CVD (HR = 2.59) in ESRD [140] . Poorer graft outcomes are predicted by IL-6 [136,141] and elevated symmetric dimethylarginine [142] (HR = 5.51). TroponinT, usually used in the diagnosis of ACS, is a strong independent predictor of allcause mortality in stable RTRs [143] .…”
Section: Inflammationmentioning
confidence: 99%
“…Data from the ALERT trial demonstrated that biomarkers such as interleukin-6 and C-reactive protein have a direct association with increased cardiovascular risk. 97 The Framingham risk factor model has not been validated in kidney transplantation and, owing to the multifactorial specificity of kidney transplant patients, it is not considered to be applicable for calculating cardiovascular risk in these populations. Therefore, there is an ongoing need for the development of a risk factor calculator that is specific to kidney transplantation.…”
Section: Cardiovascular Complications In Kidney Transplantationmentioning
confidence: 99%
“…[31][32][33] Thus, it has been postulated that statins might exert a protective effect in regards to progressive kidney damage. In theory, statins are believed to downregulate the production and renal infiltration of T-cells, T-helper cells, macrophages, and neutrophils, leading to reductions in renal inflammation, glomerular scarring, and mesangial proliferation.…”
Section: Use Of Statins In Chronic Kidney Diseasementioning
confidence: 99%
“…Inflammatory markers such as interleukin-6 and C-reactive protein are elevated in this population, and are independently associated with major cardiovascular events and all-cause mortality. 32 Due to their antiinflammatory effects and protective role in preventing ischemia-reperfusion injury, it has been hypothesized that statins may provide beneficial effects in renal transplant recipients. 57 The one major randomized trial conducted on the effects of statins on renal transplant recipients was the ALERT (Assessment of Lescol in Renal Transplant) trial.…”
Section: Statins and Renal Transplantmentioning
confidence: 99%